Usefulness of Mechanical Thrombectomy in Patients with Cancer Who Developed Cerebral Infarction - Sayaka TERAZONO; Yuki SAKAEYAMA; Yutaka FUCHINOUE; Masataka MIKAI; Shuhei KUBOTA; Mitsuyoshi ABE; Kosuke KONDO; Nobuo SUGO; Takaaki NAGAO; Masaaki NEMOTO (Neurologia Medico-Chirurgica)
Mechanical thrombectomy (MT) is an established treatment for large vessel occlusion in the acute phase of stroke. However, its efficacy and safety in patients with cancer remain unclear. This study aimed to evaluate the therapeutic effect of MT against large vessel occlusion between patients with and without cancer. A total of 71 patients who underwent MT from August 2014 to November 2021 were included in this study. Patients with cancer and/or a history of cancer (n = 16) were included in the with cancer group and the remaining patients in the without cancer group (n = 55). The frequency of preoperative tissue plasminogen activator administration was significantly lower in the with cancer group (n = 2 [12.5%]) than in the without cancer group (n = 24 [43.6%]). However, there were no significant differences between the two groups in terms of treatment time, pass frequency, thrombolysis in cerebral infarction grade, modified Rankin scale score at 1 week after treatment [mRS(1w)], modified Rankin scale score at discharge [mRS(ENT)], modified Rankin scale score at 90 days after treatment [mRS(90 days)], and length of hospital stay (days). In the multivariate analysis, if the objective variables were mRS(1w) and mRS(90 days), the National Institutes of Health Stroke Scale (NIHSS) and preonset mRS scores were considered significant variables. The presence or absence of cancer was not considered an independent factor of mRS(1w), mRS(ENT), or mRS(90 days). Aggressive treatment may be recommended to patients with cancer and/or a history of cancer who present with a systemic condition that can be managed with MT.